Synthesis and characterization of La substituted BiFeO3 - BaTiO3 composites to emphasize on their various physical properties. (2022) - Karma, Nikita; Saleem, M.; Karil, Poornima; Kaurav, Netram; Dager, H.S.
Abstract: Synthesis and different characterization of composites (1- x ) Bi0.9 La0.1 FeO3 - ( x ) BaTiO3 [ x  = 0.05, 0.10 and 0.15] are reported. The Synthesis of composites was carried out using the solid-state technique. X-ray diffraction (XRD) spectroscopy was used to examine the crystal structure and Phase formation. From XRD data analysis, both phases of the composites were witnessed. Bi0.9 La0.1 FeO3 phase was found to have crystalized in monoclinic structure (C1c1) and BaTiO3 phase has acquired cubic structure (Pm-3 m). The calculated average crystallite size of (1-x) Bi0.9 La0.1 FeO3 - (x) BaTiO3 [x = 0.05, 0.10 and 0.15], were found to be 37.73 nm, 35.80 nm and 30.35 nm, respectively. Frequency dependent room temperature dielectric studies of these composites infer that these composites are a good dielectric in nature. They exhibit a high dielectric constant with relatively lower tangential loss values. A shoulder like behavior in the dielectric loss character witnesses that these samples exhibit relaxation phenomena. The depressed semicircles observed in the electric modulus and impedance studies reveal the samples have distribution of relaxation times and exhibit non- Debye character. The Saturated polarization (Ps ) are 1.594 μC/cm 2, 2.2393 μC/cm 2 and 0.4804 μC/cm 2 respectively alongwith remnant polarization (Pr ) are 1.0407 μC/cm 2, 1.967μC/cm 2 and 0.2495 μC/cm 2 respectively for (1- x ) Bi0.9 La0.1 FeO3 - ( x ) BaTiO3 [ x  = 0.15, 0.10 and 0.05].